Potentially inappropriate medication as a predictor of poor prognosis of COVID-19 in older adults: a South Korean nationwide cohort study - Hyungmin Kim; Song Hee Hong (BMJ Open)
Objectives To investigate the association between exposure to potentially inappropriate medication (PIM) and poor prognosis of COVID-19 in older adults, controlling for comorbidity and sociodemographic factors.Design and setting Nationwide retrospective cohort study based on the national registry of COVID-19 patients, established through the linkage of South Korea’s national insurance claims database with the Korea Disease Control and Prevention Agency registry of patients with COVID-19, up to 31 July 2020.Participants A total of 2217 COVID-19 patients over 60 years of age who tested positive between 20 January 2020 and 4 June 2020. Exposure to PIM was defined based on any prescription record of PIM during the 30 days prior to the date of testing positive for COVID-19.Primary outcome measures Mortality and utilisation of critical care from the date of testing positive until the end of isolation.Results Among the 2217 COVID-19 patients over 60 years of age, 604 were exposed to PIM prior to infection. In the matched cohort of 583 pairs, PIM-exposed individuals exhibited higher rates of mortality (19.7% vs 9.8%, p<0.0001) and critical care utilisation (13.4% vs 8.9%, p=0.0156) compared with non-exposed individuals. The temporal association of PIM exposure with mortality was significant across all age groups (RR=1.68, 95% CI: 1.23~2.24), and a similar trend was observed for critical care utilisation (RR: 1.75, 95% CI: 1.26~2.39). The risk of mortality and critical care utilisation increased with exposure to a higher number of PIMs in terms of active pharmaceutical ingredients and drug categories.Conclusion Exposure to PIM exacerbates the poor outcomes of older patients with COVID-19 who are already at high risk. Effective interventions are urgently needed to address PIM exposure and improve health outcomes in this vulnerable population.